Vivências literárias do corpo na obra romanesca de Michel Houellebecq - Souza, Tiago Barbosa (2024)
This work aims to perform a comparative study of the representations of the body in Michel Houellebecq's novels, in order to understand how the construction of corporeality in his literary writing relates to the problematic of contemporary human relations. Therefore, we aim to analyze the use of literary discourse in the representation of the body according to an idea of physical fragmentation, analogous to an idea of degradation of contemporary social relations, in the structuring of Michel Houellebecq's prose, through reflection on the uses of the body and its integration with the world in the post-industrial era, based on the selected novels; the analysis of the author's thoughts regarding literary writing and his dialogues with other areas of knowledge, through the comparative method; the exploration of narrative techniques that use the body as a central operating element in the proposed novels; as well as the use of the body as part of a metaphor for states and social relations characteristic of western contemporary; and the examination of representations of the fragmented body and its function in the construction of literary discourse, in the selected corpus. This work aims, therefore, to deepen the understanding of Michel Houellebecq's work, keeping in view his way of thinking about the body and founding his artistic project on it. The study developed here considers not only the literary elements, but also the philosophical, political and sociological issues present in the author's works, which corroborate the centrality of the body and the hypothesis launched by this research. Based on the comparative method, the analysis proposed here aims to approach Michel Houellebecq's eight novels from thematic, formal and metafictional points of view. To do so, we used studies by researchers such as Barthes (2012), Dubois (2000), Bauman (1998; 2014), Le Breton (2012; 2013; 2015), Courtine and Vigarello (2011), Queval (2008), Vasseur (2004), Haraway (2000; 2006; 2016), Marx and Engels (2012), Viard (2013), Novak-Lechevalier (2018; 2022), Preciado (2018), Gazalé (2017), Foucault (2008; 2013; 2021), among others.